Розв’язування задач комбінаторної оптимізації на квантових комп’ютерах - Корольов, В.Ю.; Ходзінський, О.М. (Кібернетика та комп’ютерні технології, 2020)
Створення алгоритмів для розв’язування задач комбінаторної оптимізації для гібридних квантово-напівпровідникових обчислювальних комплексів дозволяє прискорити отримання результатів та отримати більш точні розв’язки. Розглянуто універсальні і спеціальні підходи до обчислень на квантових комп’ютерах. Наведено приклад розв’язування задачі пошуку найбільшої незалежної множини на квантових комп’ютерах IBM і D-wave, які доступні через хмарні сервіси. В работе предложены принципы классификации алгоритмов решения задач с точки зрения квантовой компьютерной математики. Показано, что количество и сила связей между кубитами влияет на размерность задач, решаемых алгоритмами квантовой компьютерной математики. Предложено рассматривать два подхода к вычислению задач комбинаторной оптимизации на квантовых компьютерах: универсальный, с помощью квантовых вентилей, и специализированный, на базе параметризации физических процессов. Приведен пример построения полусумматора для двух кубитов квантового процессора фирмы IBM и пример решения задачи поиска максимального независимого множества для квантовых компьютеров фирм IBM и D-wave. The article offers approaches to the classification of algorithms for solving these problems from the perspective of quantum computer mathematics. It is shown that the number and strength of connections between qubits affect the dimensionality of problems solved by algorithms of quantum computer mathematics. It is proposed to consider two approaches to calculating combinatorial optimization problems on quantum computers: universal, using quantum gates, and specialized, based on a parameterization of physical processes. Examples of constructing a half-adder for two qubits of an IBM quantum processor and an example of solving the problem of finding the maximum independent set for the IBM and D-wave quantum computers are given.